Role of community based rural development project on livelihood enhancement: the case of Nadowli-Kaleo District, Ghana - Christopher Tampah-Naah; Moses Naiim Fuseini; Prince Alvin Kwabena Ansah (Cogent Social Sciences)
The Community-Based Rural Development Project (CBRDP) was initially seen as a panacea for enhancing the well-being of rural communities. However, a dearth of research and the absence of adequate monitoring of the return on investment for CBRDP have prompted the need for this investigation. This study adopted a single case study design and gathered data from 36 participants, including district assembly officials and program beneficiaries, using interviews and observation. Thematic analysis was employed to analyze the data. The findings showed that the provision of agricultural infrastructure empowered the beneficiaries, leading to tangible livelihood improvements. Furthermore, rural enterprise development played a pivotal role in enhancing productivity and, consequently, livelihoods. Nonetheless, several challenges, such as funding constraints, inadequate capacity, unmet needs, and political interference, hindered the program’s implementation. Overall, while the CBRDP positively contributed to livelihood improvement, it failed to sustain these gains after the program’s conclusion. To address this, it is recommended that a bottom-up approach be employed to determine needs, the depoliticization of contract allocation, ensure timely disbursement of funds, and enhanced capacity among implementers. These measures are crucial for ensuring the sustainability of the program’s positive outcomes.